Synthesis and biological evaluation of d-gluconhydroximo-1, 5-lactam and its oxime-substituted derivatives as pharmacological chaperones for the treatment of Gaucher disease12. Issue 2 (11th January 2016) - Wang, Jiajia; Wang, Xiaomin; Zhao, Yunyan; Ma, Xiaoyao; Wan, Yue; Chen, Zhongwei; Chen, Hao; Gan, Hao; Li, Jing; Li, Lei; Wang, Peng George; Zhao, Wei
Abstract : 38 was an efficient pharmacological chaperone for GCase-related cell line N370S, which can effectively promote the activity of the mutant protein by 1.93-fold at 12.5 μM. Abstract : d -Gluconhydroximo-1, 5-lactam and its oxime-substituted derivatives were prepared and assessed for inhibition and pharmacological chaperone (PC) activities in Gaucher disease cell lines derived from N370S. The most active compound, O -(d -glucopyranosylidene) amino- Z-N -dodecylcarbamate (38 ), gave a nearly 2.0-fold increase in N370S β-GCase activity at 12.5 μM with no inhibition to other commercially available glucosidases. Docking studies of ligand–enzyme interactions have also been conducted to account for the results of enzyme activity increase. All these results demonstrate that compound38 is a promising PC for the treatment of GD.